Preparation of dry saucages by adding texture soya proteins - ΑΜΒΡΟΣΙΑΔΗΣ, Ι.; WIRTH, F. (Journal of the Hellenic Veterinary Medical Society, 2019)
Textured soya bean as a substitute of a meat part for preparation of dry saucages was studied. For this purpose dry saucages of pork meat 1/3, beef 1/3 and pork fat 1/3 were prepared. In the experimental saucages, beef was replaced by wet soya and proteins of milk. Ripening of these products continued for four weeks. The results of physical, chemical and organoleptic controls during and at the end of saucages ripening showed that addition of soya caused a rapid and strong decrease (0.1 - 0.2 units) of pH, loss of weight, colourlessness, an increase of protein content and a simultaneous decrease of water and fat. The organoleptic control showed that saucages without soya was superior to those with it as regards taste and smell. These differences, due mainly to the strong decrease of the pH of saucages with soya, were unimportant. Additional spices (garlic, nutmeg) improve these products. No strange smell or taste were observed.